THE RELATIONSHIP BETWEEN LEARNING ORIENTATION AND INNOVATION - Gattermann Perin, Marcelo; Hoffmann Sampaio, Cláudio (Revista Eletrônica de Administração, 2013)
There has been a growing interest for the learning process in the organizational context, stimulated by the perception that learning and innovation are essential for survival in competitive and dynamic environments. In spite of the number of specific publications on innovation and organizational learning, there is still an empirical gap in combining the issues together. This article investigates the relationship between innovation and organizational learning, considering the construct of learning orientation and its three dimensions: (i) commitment to learning; (ii) shared vision; and (iii) open-mindedness. A theoretical model describing the hypothetical relationships among these constructs was developed and tested using the structural equation modeling technique. The research was applied in the Brazilian Electro-Electronic Industry. Results show an appropriate adjustment of the investigated structural model, which indicates an influence of the learning orientation over the products innovation, and possibly over the competitive advantage in companies involved in learning processes. The results mainly show that the open-mindedness dimension has a stronger relationship with innovation. It indicates that an open-mindedness attitude, associated to the unlearning concept, stimulates the creation of new products and discontinuity of market standards.